Effects of aloe vera (Aloe barbadensis Miller) gel on growth performance and haemato-biochemical profiles in broiler chickens (Bangladesh Veterinarian, 2019)
The study was designed to assess the effects of aloe vera gel (AVG) on broiler growth performance and haemato-biochemical changes. “Lohman” day-old broiler chicks (n=48) were reared for 28 days. At day 13, chicks were randomly divided into four equal groups (12/group). Group A was non-treated control. Group B was supplemented with antibiotic (oxytetracycline hydrochloride) as a growth promoter in water. Group C and D were supplied AVG (1% and 2%) in drinking water. Antibiotic and AVG treated broilers had higher (P